Additive polymer and silicone hydrogel lens material

By adding the added polymer of the benzotriazole framework to the silicon hydrogel, the problem of insufficient mechanical properties of the silicon hydrogel lens material is solved, and the tensile fracture strength and toughness are significantly improved, which meets higher Requirements for use.

CN119137169APending Publication Date: 2024-12-13MENICON CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280095267.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-04-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing silicon hydrogel lens materials still have shortcomings in terms of mechanical characteristics, especially the tensile fracture strength and toughness are not ideal, which makes it difficult to meet higher usage requirements.

Method used

Added polymers containing benzotriazole skeletons but not polymerized groups are added to the silicon hydrogel, and the tensile breaking strength and toughness of the material are improved by physical assembly, with a specific addition amount of 20 out of 100 parts by mass The molar ratio is preferably from 1/1 to 4/1, and is further optimized to 2/1 to 3.5/1.

Benefits of technology

Significantly improves the tensile fracture strength and toughness of silicon hydrogel lens materials, increases tensile fracture strength of more than 10% and toughness of more than 15%, and in some cases, it reaches an increase of more than 50% or more than 100%. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0005097826570000041
    Figure BDA0005097826570000041
Patent Text Reader

Abstract

The additive polymer is added to the silicone hydrogel to improve the tensile breaking strength and toughness of the silicone hydrogel, contains a benzotriazole skeleton, and does not have a polymeric group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to additive polymer and silicone hydrogel lens materials. Background Art

[0002] Conventionally, as a silicone hydrogel lens material, a material including a copolymer component has been proposed (for example, see Patent Document 1), the copolymer component including a compound A having a group including an ethylenically unsaturated group and a polydimethylsiloxane structure via a urethane bond, an alkoxy-containing acrylate B, and a phenylalkyl acrylate or a phenoxyalkyl acrylate C. This contact lens material can provide a material that is transparent, has low adhesiveness, is safe without adsorption to the cornea during wear, is easy to handle, and has excellent shape stability due to an appropriate balance between strength and flexibility or elasticity.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2005-089654 Summary of the invention

[0006] However, although the silicone hydrogel lens material of Patent Document 1 achieves an appropriate balance between strength and flexibility or elasticity by combining compounds A to C, it is still insufficient, and further improvement of mechanical properties such as tensile strength at break and toughness is desired.

[0007] The present invention has been made in view of the above problems, and a main object of the present invention is to provide an additive polymer and a silicone hydrogel lens material capable of further improving the mechanical properties of a silicone hydrogel lens material.

[0008] As a result of intensive studies to achieve the above object, the present inventors have found that when an addition-type polymer having a benzotriazole skeleton and having no polymerizable group is added to a silicone hydrogel within a predetermined range, the mechanical properties can be further improved, thereby completing the present invention.

[0009] That is, the additive polymer of the present invention is an additive polymer added to the silicone hydrogel to improve the tensile strength and toughness of the silicone hydrogel.

[0010] It contains a benzotriazole skeleton and has no polymerizing group.

[0011] The silicone hydrogel lens material of the present invention comprises:

[0012] Silicone hydrogel substrate, and

[0013] The above-mentioned additive polymer;

[0014] The additive polymer is contained in an amount of 20 parts by mass or less based on 100 parts by mass of the substrate.

[0015] The additive polymer and silicone hydrogel lens material of the present invention can further improve mechanical properties. The reason for obtaining such an effect is speculated as follows. For example, it is speculated that by physically incorporating an additive polymer containing a benzotriazole skeleton having no polymerizable group into the structure of the silicone hydrogel base material, mechanical properties such as tensile strength at break and toughness are improved. DETAILED DESCRIPTION

[0016] <Additive polymer>

[0017] The additive polymer disclosed in the present embodiment is an additive polymer added to the silicone hydrogel to improve the tensile strength and toughness of the silicone hydrogel, and contains a benzotriazole skeleton and does not have a polymerizing group. Here, as a polymerizing group that the additive polymer does not have, for example, refers to a group that is polymerized such as vinyl, acryloyl and methacryloyl, and does not contain a hydroxyl group, an aromatic ring, or a heterocycle. In addition, acrylates with acryloyl groups and methacrylates with methacryloyl groups are collectively referred to as "(meth)acrylates" below. Furthermore, below, for ease of explanation, the constituent parts contained in the polymer are specified by the name of the monomer, and the monomers exemplified in the description of the structure of the polymer are set to a structure in which its polymerizing group is bonded to other constituent parts. For example, in the description of the structure of the polymer, taking "(meth)acrylate" as an example, it exists in the polymer in the form of a "(meth)acrylate structure", which is a structure in which other constituent parts are double-bonded (polymerized) to (meth)acrylate.

[0018] The additive polymer preferably has the same structural part as the part constituting the substrate of the silicone hydrogel. If it has such a structural part, the compatibility of the silicone hydrogel with the monomer can be further improved. The structural part can include, for example, a silicone part having a siloxane bond, an amide part having an amide bond, an ether part having an ether bond, an ester part having an ester bond, etc. The structural part can include one or more of the structures of the monomers of the substrate described later, for example, the structure of acrylamide-based hydrophilic monomers such as N-vinyl-2-pyrrolidone (N-VP), 1-methyl-3-methylene-2-pyrrolidone (N-MMP) and N, N-dimethylacrylamide (DMAA), etc. Among them, the structural part is preferably a silicone part. For example, the additive polymer can have a structure in which a triazole part A containing a benzotriazole skeleton and a silicone part B having a siloxane bond are bonded by a carbon chain. The silicone part B can be the same as the part constituting the substrate of the silicone hydrogel. The benzotriazole part A can be, for example, a structure in which the benzotriazole skeleton is bonded to a carbon chain via an aromatic ring and a bonding chain. The aromatic ring can be a benzene ring having one or more substituents, and as the substituent, for example, it can be one or more of a hydroxyl group, an alkyl group having 6 or less carbon atoms, an acyl group having 6 or less carbon atoms, etc. As the bonding chain, an alkyl chain having 6 or less carbon atoms can be cited, and the bonding chain can include an ester bond.

[0019] The silicone part B may have a silicone-containing (meth) alkyl acrylate structure, for example. Examples of the silicone part B include trimethylsiloxydimethylsilylmethyl (meth)acrylate, trimethylsiloxydimethylsilylpropyl (meth)acrylate, methylbis(trimethylsiloxy)silylpropyl (meth)acrylate, tris(trimethylsiloxy)silylpropyl (meth)acrylate, mono[methylbis(trimethylsiloxy)siloxy]bis(trimethylsiloxy)silylpropyl (meth)acrylate, tris[methylbis(trimethylsiloxy)siloxy]silylpropyl (meth)acrylate, methylbis(trimethylsiloxy)silylpropyl glyceryl (meth)acrylate, tris(trimethylsiloxy)silylpropyl glyceryl (meth)acrylate, and tris(trimethylsiloxy)silylpropyl glyceryl (meth)acrylate. Mono[methylbis(trimethylsiloxy)silyloxy]bis(trimethylsiloxy)silylpropylglyceryl(meth)acrylate, trimethylsilylethyltetramethyldisiloxypropylglyceryl(meth)acrylate, trimethylsilylmethyl(meth)acrylate, trimethylsilylpropyl(meth)acrylate, trimethylsilylpropylglyceryl(meth)acrylate, trimethylsiloxydimethylsilylpropylglyceryl(meth)acrylate, methylbis(trimethylsiloxy)silylethyltetramethyldisiloxymethyl(meth)acrylate, tetramethyltriisopropylcyclotetrasiloxypropylpropyl(meth)acrylate, tetramethyltriisopropylcyclotetrasiloxybis(trimethylsiloxy)silylpropylpropyl(meth)acrylate, etc. Among them, tris(trimethylsiloxy)silylpropylmethacrylate (TRIS) is preferred from the viewpoint of easy availability.

[0020] The additive polymer preferably has a structure represented by formula (1). In formula (1), m and n are integers, and R 1 , R 2 and R 3 is any group, R 1 and R 3 They may be different groups or the same group, but are more preferably the same group. 2 It may be one or more of hydrogen, hydroxyl, alkyl and acyl. The alkyl and acyl groups preferably have 6 or less carbon atoms. 1 and R 3represents a bonding chain, and examples thereof include an alkyl chain having 6 or less carbon atoms, and the bonding chain may include an ester bond. In formula (1), the triazole part A and the silicone part B may be bonded to the carbon chain in any order. In formula (1), the carbon chain to which the triazole part A and the silicone part B are bonded may be an alkyl chain having 1 to 6 or less carbon atoms. More specifically, the additive polymer preferably has a structure represented by formula (2). It should be noted that in formulas (1) and (2), the triazole part A and the silicone part B may be bonded to the carbon chain arbitrarily, and the triazole part A and the triazole part A may be adjacent to each other for 2 or more times, or the silicone part B and the silicone part B may be adjacent to each other for 2 or more times. The molar ratio m / n of the triazole part A (m) to the silicone part B (n) having a siloxane bond is preferably in the range of 1 / 1 to 4 / 1. In this range, the tensile strength and toughness of the silicone hydrogel can be further improved. The molar ratio is more preferably in the range of 2 / 1 to 3.5 / 1.

[0021]

[0022] The additive polymer is preferably added to the silicone hydrogel lens material in a range of more than 0 parts by mass and less than 20 parts by mass relative to 100 parts by mass of the silicone hydrogel substrate. In this range, the tensile strength and toughness of the silicone hydrogel can be further improved. The content of the additive polymer is preferably more than 0.1 parts by mass, more preferably more than 0.2 parts by mass, and more preferably more than 0.5 parts by mass. In addition, the content of the additive polymer is preferably less than 15 parts by mass, more preferably less than 10 parts by mass, and more preferably less than 5 parts by mass. When the additive polymer is added to the silicone hydrogel, the tensile strength can be increased by more than 10% and the toughness can be increased by more than 15% compared to the silicone hydrogel without the additive polymer. The addition effect of the additive polymer can increase the tensile strength by more than 50%, or by more than 100%. In addition, the addition effect of the additive polymer can increase the toughness by more than 50%, or by more than 100%.

[0023] Next, the method for producing the additive polymer is described. The production method may include, for example, a polymerization step of polymerizing a raw material monomer containing at least a monomer containing a benzotriazole skeleton. The raw material monomer may include a monomer having a part constituting the substrate of the silicone hydrogel. As the monomer containing the constituent part of the substrate, silicone monomers having a siloxane bond, monomers having an amide bond, monomers having an ether bond, monomers having an ester bond, etc. can be cited, among which silicone monomers are preferred. As the raw material monomer, a monomer having the structure described in the above-mentioned additive polymer can be used. The mixing ratio of the raw material monomer is, for example, preferably a mixing ratio of 1 / 1 to 4 / 1, and more preferably 2 / 1 to 3.5 / 1, in which the molar ratio m / n of the polymerization product of the monomer (m) containing a benzotriazole skeleton and the monomer (n) having the same constituent part as the substrate. As a polymerization method, free radical polymerization using a free radical polymerization initiator can be cited. As a free radical polymerization initiator, for example, azo compounds, peroxide compounds, dihalogens, etc. can be cited. As azo compounds, for example, azobisisobutyronitrile (AIBN), 1,1'-azobis(cyclohexanecarbonitrile) (ABCN) and the like can be cited. In addition, as peroxide compounds, benzoyl peroxide, methyl ethyl ketone peroxide and the like can be cited. In addition, as dihalogens, chlorine molecules and the like can be cited. The amount of the polymerization initiator used is preferably 0.001 to 2 parts by mass, and more preferably 0.01 to 1 part by mass, relative to 100 parts by mass of the raw material monomer.

[0024] <Silicone hydrogel lens material>

[0025] The silicone hydrogel lens material disclosed in this embodiment includes a silicone hydrogel substrate and the above-mentioned additive polymer. The additive polymer is included in a range of more than 0 mass parts and less than 20 mass parts relative to 100 mass parts of the substrate. The content of the additive polymer is preferably 0.1 mass parts or more, more preferably 0.2 mass parts or more, and further preferably 0.5 mass parts or more relative to 100 mass parts of the substrate. In addition, the content of the additive polymer is more preferably 15 mass parts or less, and further preferably 10 mass parts or less relative to 100 mass parts of the substrate. Compared with silicone hydrogel without the addition of additive polymer, the tensile breaking strength of the silicone hydrogel lens material can be increased by more than 10%, and the toughness can be increased by more than 15%. Compared with silicone hydrogel without the addition of additive polymer, the tensile breaking strength of the silicone hydrogel lens material can be increased by more than 50%, or more than 100%. In addition, compared with silicone hydrogel without the addition of additive polymer, the toughness of the silicone hydrogel lens material can be increased by more than 50%, or more than 100%. This improvement effect can be adjusted by the structure and content of the additive polymer.

[0026] The base material of the silicone hydrogel lens material may contain silicone parts with siloxane bonds, amide parts with amide bonds, ether parts with ether bonds, ester parts with ester bonds, etc. These constituent parts may be structures formed by polymerizing silicone macromers with siloxane bonds or silicone monomers, monomers with amide bonds, monomers with ether bonds, monomers with ester bonds, etc. Each monomer has a polymerizing group such as vinyl, acryloyl, and methacryloyl, and the base material of the silicone hydrogel has a structure formed by polymerizing the polymerizing group, such as a silicone macromer structure, a silicone monomer structure, etc.

[0027] The silicone macromer structure may have a structure including at least a urethane bond, an ether bond, an ester bond, and a polydimethylsiloxane moiety. The silicone macromer may have a structure of formula (3). In the silicone macromer structure, a is an integer of 30 to 50. R 4 , R 5 is one or more of an alkyl group and an alkyl group substituted with a halogen, and each of the one or more may be different groups or the same group. 4 , R 5 The number of carbon atoms is preferably 6 or less. As a substituent of the halogen, for example, chlorine, fluorine, etc. can be mentioned, preferably fluorine. In addition, as a specific example of the silicone macromer structure, for example, the structure of formula (4) and (5) can be mentioned. The content of the silicone macromer is preferably in the range of 5% to 40% by mass relative to the entire substrate. In this range, oxygen permeability and flexibility can be further improved, and on the other hand, polymerizability can be further improved, so it is preferred.

[0028]

[0029] Wherein, a is an integer from 30 to 50, R 4 , R 5 It is any one or more of an alkyl group and an alkyl group substituted with a halogen, and the respective one or more may be different groups or the same group.

[0030]

[0031] As the silicone monomer structure, for example, one or more of the monomers described in the silicone part B can be cited. The content of the silicone monomer structure is preferably in the range of 10% to 40% by mass relative to the entire substrate. In this range, oxygen permeability and flexibility can be further improved, and on the other hand, polymerizability can be improved, which is preferred.

[0032] As a monomer structure having an amide bond, for example, it can be a structure formed by polymerization of an amide compound (monomer) having a polymerizable group. As the monomer, for example, N, N-dimethyl (meth) acrylamide, N, N-diethyl (meth) acrylamide, N, N-dipropyl (meth) acrylamide, N, N-dimethylaminopropyl (meth) acrylamide, N, N-diethylaminopropyl (meth) acrylamide, etc. can be cited. Among them, N, N-dimethyl acrylamide (DMAA) is preferred. In addition, as a hydrophilic structure, for example, unsaturated carboxylic acids such as methacrylic acid and acrylic acid, alcohols substituted with acrylic acid such as 2-hydroxyethyl methacrylate and 2-hydroxyethyl acrylate, 1-methyl-3-methylene-2-pyrrolidone (N-MMP), vinyl lactams such as N-vinyl-2-pyrrolidone (N-VP), (meth) acrylates having a polyethylene glycol portion, etc. The content of the monomer is preferably in the range of 40% by mass or less relative to the entire substrate. When the content is within this range, the water content can be further prevented from becoming too high, and the dry feeling can be further prevented from being affected. The content is preferably 10% by mass or more. When the content is 10% by mass or more, sufficient hydrophilicity can be obtained.

[0033] As the monomer structure having an ether bond, for example, structures such as methoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxytetraethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and hydroxydiethylene glycol (meth)acrylate can be cited. Among them, methoxyethyl acrylate (2-MTA) is preferred. The content of the monomer is preferably in the range of 10% to 40% by mass relative to the entire substrate.

[0034] In addition to the substrate, the silicone hydrogel lens material may further include: a cross-linked structure formed by polymerization of a cross-linking agent having a plurality of polymerization groups, a pigment structure formed by polymerization of a pigment having a polymerization group, and the like. As the cross-linked structure, for example, allyl (meth)acrylate, vinyl (meth)acrylate, 4-vinyl benzyl (meth)acrylate, 3-vinyl benzyl (meth)acrylate, (meth)acryloyloxyethyl (meth)acrylate, ethylene glycol di(meth)acrylate, diallyl adipate, diethylene glycol di(meth)acrylate, diethylene glycol diallyl ether, triethylene glycol di(meth)acrylate and the like structures can be cited. Among them, allyl methacrylate (AMA), ethylene glycol dimethacrylate (EDMA), and the like are preferred. The content of the cross-linked structure is preferably in the range of 0.05 to 1 parts by mass relative to 100 parts by mass of the substrate as a whole.

[0035] Examples of the pigment structure include phthalocyanine-containing polymethacrylate and other phthalocyanine-containing polymeric pigments, azo-based polymeric pigments such as 1-phenylazo-4-(meth)acryloyloxynaphthalene, anthraquinone-based polymeric pigments such as 1,5-bis((meth)acryloylamino)-9,10-anthraquinone, 1,4-bis(4-(2-methacryloyloxyethyl))phenylaminoanthraquinone (Reactive Blue 246), and 1,4-bis((2-hydroxyethyl)amino)-9,10-anthracenedione (Reactive Blue 247), and nitro-based polymeric pigments such as o-nitroanilinomethyl (meth)acrylate. Among them, phthalocyanine-based polymeric pigments are preferred. Examples of phthalocyanine-based polymeric pigments include (meth)acryloyl tetraaminocopper phthalocyanine and (meth)acryloyl (dodecanoyl tetraaminocopper phthalocyanine). Furthermore, it may contain benzophenone-based polymerizable ultraviolet absorbing pigments such as 2,4-dihydroxy-3 (p-styrylazo) benzophenone, benzoic acid-based polymerizable ultraviolet absorbing pigments such as 2-hydroxy-4- (p-styrylazo) phenyl benzoate, etc. The content of the pigment structure is preferably in the range of 0.05 to 1 parts by mass relative to 100 parts by mass of the entire substrate.

[0036] The water content of the silicone hydrogel lens material is preferably in the range of 40% to 70% by mass, more preferably 60% or less by mass, and further preferably 50% or less by mass. When the water content is 40% or more by mass, the water wettability of the lens material can be improved. When the water content is 70% or less by mass, the shape maintenance can be further improved.

[0037] The refractive index of the silicone hydrogel lens material is preferably 1.2 or more, more preferably 1.4 or more. As an ophthalmic lens, the refractive index is preferably higher.

[0038] The oxygen permeability coefficient Dk value of the silicone hydrogel lens material is preferably 20 or more, and more preferably 50 or more. The higher the oxygen permeability coefficient, the more preferred it is for ophthalmic lens use. -11 (cm 2 / sec)·(mLO2 / (mL·mmHg)).

[0039] The light transmittance of the silicone hydrogel lens material is preferably 95% or more, more preferably 96% or more. As an ophthalmic lens, the light transmittance is preferably higher.

[0040] Next, the method for producing the silicone hydrogel lens material is described. The method may include, for example, a polymerization step of mixing a substrate monomer that will become a substrate of the silicone hydrogel and an additive polymer that does not have a polymerizable group and polymerizing the substrate monomer. The substrate monomer may include a silicone compound having a polymerizable group and a siloxane bond, an amide compound having a polymerizable group and an amide bond, an ether compound having a polymerizable group and an ether bond, and the like. It should be noted that the mixing ratio of each raw material component may be within the range described in the above silicone hydrogel lens material.

[0041] As the silicone compound, for example, the above-mentioned silicone macromer, silicone monomer, etc. can be cited. For example, the silicone macromer can be a compound containing at least a urethane bond, an ether bond, an ester bond and a polydimethylsiloxane part. As the silicone macromer, it can have a structure of formula (6). As a specific example of the silicone macromer, for example, formula (7), (8) and the like can be cited. As the silicone monomer, a monomer having any of the structures described in the above-mentioned silicone part B can be cited. Among them, tris(trimethylsiloxy)silylpropyl methacrylate (TRIS) is preferred.

[0042]

[0043] Wherein, a is an integer from 30 to 50, R 4 , R 5 It is any one or more of an alkyl group and an alkyl group substituted with a halogen, and the respective one or more may be different groups or the same group.

[0044]

[0045] As the amide compound, there can be mentioned monomers containing any of the structures described in the monomer structure having an amide bond. Among them, N,N-dimethylacrylamide (DMAA) is preferred. In addition, as the hydrophilic monomer, for example, unsaturated carboxylic acids such as methacrylic acid and acrylic acid, alcohols substituted with acrylic acid such as 2-hydroxyethyl methacrylate and 2-hydroxyethyl acrylate, vinyl lactams such as 1-methyl-3-methylene-2-pyrrolidone and N-vinylpyrrolidone, (meth)acrylates having a polyethylene glycol moiety, etc. can be used.

[0046] Examples of the ether compound include monomers having any of the structures described in the monomer structure having an ether bond, etc. Among them, methoxyethyl acrylate (2-MTA) is preferred.

[0047] In addition, in this polymerization process, except the substrate monomer, crosslinking agent, polymerizable pigment, polymerization initiator etc. can also be further added. As crosslinking agent, any compound in each structure described in the above-mentioned crosslinked structure can be used. In addition, as polymerizable pigment, any compound in each structure described in the above-mentioned pigment structure can be used. In addition, in this polymerization process, non-polymerizable water-soluble organic solvent, surfactant, cooling agent, thickening agent etc. can be used as additive.

[0048] In the polymerization process of the silicone hydrogel lens material, thermal polymerization, photopolymerization, etc. can be performed. As a polymerization initiator, a thermal polymerization initiator, a photopolymerization initiator, etc. can be used. For example, when the amount of the additive polymer is relatively large, such as 5 parts by mass or more, relative to 100 parts by mass of the entire substrate, a thermal polymerization initiator is preferably used, and when the amount of the additive polymer is relatively small, such as less than 5 parts by mass, a photopolymerization initiator is preferably used. As a thermal polymerization initiator, for example, 2,2'-azobisisobutyronitrile, 2,2'-azobis-(2,4-dimethylvaleronitrile) (V-65), benzoyl peroxide, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, lauroyl peroxide, tert-butyl peroxyhexanoate, 3,5,5-trimethylhexanoyl peroxide, etc. can be cited. These thermal polymerization initiators can be used alone or in combination of two or more. As the photopolymerization initiator, for example, phosphine oxide-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzophenone-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, etc. can be mentioned. As the phosphine oxide-based photopolymerization initiator, for example, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, etc. can be mentioned. As the benzoin-based photopolymerization initiator, for example, methyl o-benzoylbenzoate, methyl benzoylformate, etc. can be mentioned. As the benzophenone-based photopolymerization initiator, for example, 2-hydroxy-2-methyl-1-phenylpropane-1-one (HMPPO), p-isopropyl-α-hydroxyisobutylbenzophenone, etc. can be mentioned. As the thioxanthone-based photopolymerization initiator, for example, 2-chlorothioxanthone, 2-methylthioxanthone, etc. can be mentioned. These photopolymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.001 to 2 parts by mass, more preferably 0.01 to 1 part by mass, based on 100 parts by mass of the substrate monomer.

[0049] In the polymerization process, the raw material composition can be cured by a casting method. In the case of heating the raw material composition to polymerize it, it is sufficient to fill the raw material composition containing the above-mentioned thermal polymerization initiator in a casting mold corresponding to the shape of the desired ophthalmic lens material, and then heat the casting mold to polymerize it. The material of the casting mold can be any material that can withstand the temperature required for polymerization and curing. In addition, in the case of irradiating the raw material composition with light to polymerize it, it is sufficient to fill the raw material composition containing the above-mentioned photopolymerization initiator in a casting mold corresponding to the shape of the desired ophthalmic lens material, and then irradiate the casting mold with light to polymerize it. The material of the casting mold used in the polymerization by light irradiation is not particularly limited as long as it is a material that can transmit the light required for polymerization and curing. It is preferably a general-purpose resin such as polypropylene, polystyrene, nylon, polyester, or glass.

[0050] It is speculated that in the additive polymer and silicone hydrogel lens material of the present embodiment described in detail above, for example, by physically incorporating the additive polymer including the benzotriazole skeleton having no polymerizing group into the structure of the silicone hydrogel base material, mechanical properties such as tensile strength at break and toughness are improved. In addition, the benzotriazole skeleton has a low acid dissociation constant (pKa), and is believed to interact with surrounding amide bonds in the lens material, etc., to enhance mechanical strength.

[0051] It should be noted that the present invention is not limited to the above-mentioned embodiments, and can be implemented in various forms as long as they fall within the technical scope of the present invention.

[0052] Example

[0053] Hereinafter, examples of the silicone hydrogel lens material of the present invention will be described as experimental examples. Experimental examples 5 to 10 and 12 are equivalent to the embodiments of the present invention, and experimental examples 1 to 4 and 11 are equivalent to comparative examples. It should be noted that the present invention is not limited to the following embodiments, and can be implemented in various ways as long as it falls within the technical scope of the present invention.

[0054] [Ingredients used]

[0055] The abbreviations of the compounds used in the Examples are shown below.

[0056] <Base material>

[0057] Silicone macromer: silicone compound represented by formula (7)

[0058] TRIS: Tris(trimethylsiloxy)silylpropyl methacrylate

[0059] N-VP: N-vinyl-2-pyrrolidone

[0060] N-MMP: 1-methyl-3-methylene-2-pyrrolidone

[0061] 2-MTA: 2-methoxyethyl acrylate

[0062] DMAA: N, N-dimethylacrylamide

[0063] <Cross-linking agent>

[0064] AMA: Allyl Methacrylate

[0065] EDMA: Ethylene glycol dimethacrylate

[0066] <Polymerization initiator>

[0067] TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide

[0068] V-65: 2,2'-azobis-(2,4-dimethylvaleronitrile)

[0069] <Pigment>

[0070] PCPMA: Polymethacrylate containing phthalocyanine

[0071] RB-247: 1,4-bis((2-hydroxyethyl)amino)-9,10-anthracenedione

[0072] <Monomers for additive polymers>

[0073] Benz-M: 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole

[0074] <Comparative polymer>

[0075] TMSSt: tris(trimethylsiloxy)silylstyrene

[0076] [Synthesis of Additive Polymers 1 to 4]

[0077] 7 g of Benz-M and 5 g of TRIS (molar ratio = 1.84:1) were weighed into a 200 mL three-necked flask (reaction vessel) and dissolved in 50 mL of toluene. The reaction vessel was placed in an oil bath heated to 80°C. After confirming that the internal liquid temperature was 80°C, 0.60 g of azobisisobutyronitrile (AIBN) dissolved in 15 mL of toluene was quickly added to start the reaction. After 24 hours, the reaction vessel was removed from the oil bath and cooled to room temperature. Then, the reaction solution was added dropwise to 1 L of methanol stirred in a beaker at a rate of 2 drops / second using a dropping funnel to precipitate a polymer. After suction filtration using a glass funnel, it was washed twice with 100 mL of methanol and dried in a reduced pressure dryer at 50°C for 1 hour to obtain about 6 g of white solid additive polymer 1. In addition, using a monomer obtained by acetylation of the phenolic OH of Benz-M, additive polymer 2 was obtained through the same process as above. In addition, polymers obtained by using monomers with a changed ratio of Benz-M to TRIS were used as additive polymers 3 and 4. The molar ratio of the triazole part (Benz-M part) to the silicone part (TRIS part) of additive polymers 1 and 2 was 2.7:1, and the content of the triazole part relative to the whole was 73% by mass. In addition, the molar ratio of the triazole part (Benz-M part) to the silicone part (TRIS part) of additive polymers 3 and 4 was 3.1:1 and 2.2:1, respectively.

[0078] [Synthesis of Comparative Polymers 1 to 3]

[0079] Comparative polymers were prepared using TRIS, N-VP, DMAA and TMSSt as monomers in the same manner as the addition type polymer at the mass ratios shown in Table 1. Table 1 summarizes the composition, weight average molecular weight Mw, number average molecular weight Mn and Mw / Mn of the prepared polymers.

[0080] [Table 1]

[0081] polymer constitute M Mn Mw / Mn Additive polymer 1 Benz-M:TRIS=2.7:1 (molar ratio) 7000 4800 1.46 Additive polymer 2 <![CDATA[Benz-M ※ :TRIS=2.7:1(molar ratio)]]> 7000 4800 1.46 Additive polymer 3 Benz-M:TRIS=3.1:1 (molar ratio) 7610 5350 1.42 Additive polymer 4 Benz-M:TRIS=2.2:1 (molar ratio) 8700 5560 1.56 Comparison polymer 1 TRIS: N-VP = 3:1 (mass ratio) 6200 4800 1.29 Comparison polymer 2 TRIS:DMAA=2:1 (mass ratio) 16000 10200 1.57 Comparison polymer 3 TMSSt:DMAA=1:1(mass ratio) 6000 3900 1.54

[0082] ※Additive polymer 2: A polymer obtained by acetylation of the phenolic OH group of additive polymer 1

[0083] [Compounding and polymerization of silicone hydrogel]

[0084] The polymer obtained above is preliminarily dissolved in monomers that are easily compatible and used in large quantities in the contact lens formulation, and the monomers shown in Table 2 are mixed in an appropriate order to prepare a contact lens formulation. It should be noted that in order to suppress the moisture absorption of the monomers during weighing, the monomers are weighed in sequence starting from the hydrophobic monomers. The polymerization initiator used is selected from a thermal polymerization initiator (azo system: V-65) or a photopolymerization initiator (phosphine oxide system: TPO). For compositions containing a large amount of benzotriazole-based additive polymers in the formulation (experimental examples 6 to 8), thermal polymerization is carried out using a thermal polymerization initiator. For a small amount of additive polymers (about 1% in the formulation: experimental examples 1 to 5, 9 to 12), a photopolymerization initiator is selected. The prepared formulation is cast into a lens mold. Thermal polymerization is carried out in a dryer set at 80°C for 2 hours. A light source containing blue light is used for photopolymerization, and an appropriate illumination (illuminance 2.5 to 3.5 mW / cm 2 ) and irradiated for 20 minutes to carry out polymerization.

[0085] [Hydration treatment]

[0086] After demolding, the obtained polymer was subjected to plasma irradiation for 120 seconds in a carbon dioxide atmosphere (RF output 50W, pressure 100Pa). It was immersed in distilled water to absorb water for hydration treatment, and then sterilized by heating in an autoclave (2 atmospheres, 121°C, 20 minutes) to obtain a contact lens. The obtained silicone hydrogel contact lenses were used as Experimental Examples 1 to 12. The compounding ratios of Experimental Examples 1 to 12 are summarized in Table 2.

[0087] [Table 2]

[0088]

[0089] (Strength measurement)

[0090] The tensile test of lens fragments (thickness 0.1 mm, width 1.8 mm, distance between fixtures 6.0 mm) at 20°C was carried out in ISO physiological saline using a tensile tester Autograph AG-IS manufactured by Shimadzu Corporation. The test was carried out on 5 or more lenses / batch, and the tensile fracture strength was calculated from the maximum load until fracture and the thickness and width of the lens fragments, and the toughness was calculated from the fracture energy, the thickness and width of the lens fragments, and the distance between the fixtures.

[0091] (Water content)

[0092] The water content (mass %) of the lens was measured in ISO saline at 20°C according to the following formula: W represents the mass (g) of the lens in the equilibrium state after state adjustment, and W0 represents the mass (g) of the lens dried in a desiccator at 105°C for 16 hours.

[0093] Water content (mass %) = (W-W0) / W×100

[0094] (Refractive Index)

[0095] The refractive index of mercury-e-ray was measured in ISO physiological saline at a temperature of 20° C. using a refractometer 2T manufactured by ATAGO Corporation.

[0096] (Dk (oxygen permeability) value)

[0097] The oxygen permeability coefficient of the lens was measured in 35°C ISO physiological saline using a membrane oxygen permeability meter manufactured by Rika Seiki Kogyo Co., Ltd. according to the electrode method described in ISO18369-4 (2006). The unit of Dk value is 10 -11 (cm 2 / sec)·(mLO2 / (mL·mmHg)).

[0098] (Light transmittance)

[0099] The light transmittance of the lens in ISO saline was measured using UV-2550 manufactured by Shimadzu Corporation. The measurement conditions were set to transmittance (0-100%), slit 5nm, and measurement wavelength 780-380nm. The lens holder was set in a quartz cell to measure the light transmission spectrum. The light transmittance (780-380nm) was obtained by data processing.

[0100] (Results and Investigation)

[0101] The moisture content (mass %), refractive index, Dk value, and light transmittance (%) of silicone hydrogels 1 and 2 (experimental examples 1 and 11) are summarized in Table 3. The moisture content and refractive index of silicone hydrogels 1 and 2 are both appropriate, and they show high oxygen permeability and light transmittance. In addition, the composition of each experimental example, the amount of polymer added (mass %), the tensile strength at break (MPa), the rate of change (%) relative to the control (experimental examples 1 and 11) without adding a polymer, the toughness (MPa), and the rate of change (%) relative to the control are summarized in Tables 4 to 6. It should be noted that the strains of Experimental Examples 1, 9, and 10 are 500%, 563%, and 515%, respectively, and the elastic moduli are 0.23MPa, 0.24MPa, and 0.25MPa, respectively. As shown in Table 4, the tensile strength at break and the toughness of Experimental Examples 2 to 4 to which comparative polymers 1 to 3 are added are lower than those of Experimental Example 1 to which no polymer is added. In contrast, in Experimental Examples 5 to 8, in which additive polymers 1 and 2 were added, the tensile strength at break and toughness were significantly improved to a change rate of 50% or more compared to Experimental Example 1 without adding a polymer. In addition, in Experimental Examples 9 and 10, in which additive polymers 3 and 4 were added, the tensile strength at break and toughness were improved to a change rate of 15% or more compared to Experimental Example 1 without adding a polymer. According to the results of Experimental Examples 5 to 10, it can be seen that even if the mixing ratio of Benz-M and TRIS in the additive polymer is different, the tensile strength at break and toughness are improved. In particular, it can be seen that in the additive polymer, the molar ratio m / n of the triazole part A (m) and the silicone part B (n) having a siloxane bond is preferably in the range of 1 / 1 to 4 / 1, and more preferably in the range of 2 / 1 to 3.5 / 1. According to the results of Experimental Examples 5 to 12, it can be seen that even in silicone hydrogels 1 and 2, that is, the composition of the hydrogel is different, the addition effect of the additive polymer is confirmed. In particular, it was found that the amount of the additive polymers 1 to 4 added is more preferably in the range of 10 parts by mass or less relative to 100 parts by mass of the silicone hydrogel base material.

[0102] In addition, the compatibility of the additive polymer and the silicone hydrogel was studied. Benz-M homopolymer was mixed into the monomer solution of silicone hydrogel 3 as an additive polymer. As a result, the homopolymer did not dissolve in the solution. Therefore, it can be seen that the additive polymer preferably has the same structural part as the part constituting the base material of the silicone hydrogel.

[0103] [Table 3]

[0104]

[0105] ※Unit is 10 -11 (cm 2 / sec)·(mLO2 / (mL×mmHg))

[0106] [Table 4]

[0107]

[0108] [Table 5]

[0109]

[0110] [Table 6]

[0111]

[0112] Industrial Applicability

[0113] The additive polymer of the present invention can be used in silicone gel contact lenses.

Claims

1. An additive polymer is added to the silicone hydrogel to improve the tensile strength and toughness of the silicone hydrogel. It contains a benzotriazole skeleton and has no polymerizing group.

2. The additive polymer according to claim 1, wherein It has a structure in which a triazole part including the benzotriazole skeleton and a silicone part having a siloxane bond are bonded via a carbon chain.

3. The addition polymer according to claim 1 or 2, wherein Having the structure shown in formula (1), The triazole part A and the silicone part B are bonded to the carbon chain in any order, m and n are integers, and R 1 , R 2 and R 3 is any group, R 1 and R 3 It can be different groups or the same group, R 2 It is one or more of hydrogen, hydroxy, alkyl and acyl.

4. The addition polymer according to any one of claims 1 to 3, wherein The silicone hydrogel has the same constituent parts as those constituting the base material of the silicone hydrogel.

5. A silicone hydrogel lens material, comprising: Silicone hydrogel substrate, and The addition polymer according to any one of claims 1 to 4; The additive polymer is contained in an amount of 20 parts by mass or less based on 100 parts by mass of the substrate.

6. The silicone hydrogel lens material according to claim 5, wherein: The base material of the silicone hydrogel has a structure of formula (2), Wherein, a is an integer from 30 to 50, R 4 , R 5 It is any one or more of an alkyl group and an alkyl group substituted with a halogen, and the respective one or more may be different groups or the same group.

7. The silicone hydrogel lens material according to claim 5 or 6, wherein: Compared with the silicone hydrogel without the additive polymer, the tensile breaking strength of the silicone hydrogel lens material is increased by more than 10%, and the toughness is increased by more than 15%.

Citation Information

Patent Citations

  • Ocular lens material

    JP2005089654A